Polityka rozwoju obszarów wiejskich w regionie metropolitalnym - Chmielewska, Barbara (Development Policy of Rural Areas in A Metropolitan Region, 2009)
A metropolitan area is characterized by well developed areas localized around the big city and by backwards, remote areas. In such a region the most important is to take measures to ensure sustainable growth. Development policy of such a region should be a cohesion and convergence policy. It means realization of policy that includes well-balanced economic, social and environmental goals, farming and non-farming activity. Maintenance of rural areas vitality is one of important goals. In this purpose improvement of rural infra-structure and investment in human capital are indispensable. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 552-559